The Impact of Board Gender Diversity and Ownership structure on ESG Disclosure - Diah Yulia Paramita, Kadek; Gede Krisna Dewi, Luh (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This research is intended to investigate the impact of board gender diversity, managerial ownership and institutional ownership on ESG disclosure. Research was conducted on SRI-KEHATI indexed issuers for the 2019-2023 period. A sample of 133 observations was determined using a purposive sampling technique. Multiple linear regression analysis techniques using SPSS version 25 were used to carry out testing. The results prove that board gender diversity has no effect on ESG disclosure, while managerial ownership and institutional ownership have a positive effect on ESG disclosure. The implications of this research support stakeholder theory and the concept of corporate governance and provide suggestions for issuers, investors, regulators, and future research related to ESG disclosure.